Masking and unmasking of the sialic acid-binding lectin activity of CD22 (Siglec-2) on B lymphocytes - Razi, Nahid (The National Academy of Sciences, 1998)
CD22 is a B cell-restricted glycoprotein involved in signal transduction and modulation of cellular activation. It is also an I-type lectin (now designated Siglec-2), whose extracellular domain can specifically recognize α2–6-linked sialic acid (Sia) residues. This activity is postulated to mediate intercellular adhesion and/or to act as a coreceptor in antigen-induced B cell activation. However, studies with recombinant CD22 indicate that the lectin function can be inactivated by expression of α2–6-linked Sia residues on the same cell surface. To explore whether this masking phenomenon affects native CD22 on B cells, we first developed a probe to detect the lectin activity of recombinant CD22 expressed on Chinese hamster ovary cells (which have no endogenous α2–6-linked Sia residues). This probe is inactive against CD22-positive B lymphoma cells and Epstein–Barr virus-transformed lymphoblasts which express high levels of α2–6-linked Sia residues. Enzymatic desialylation unmasks the CD22 lectin activity, indicating that endogenous Sia residues block the CD22 lectin-binding site. Truncation of the side chains of cell surface Sia residues by mild periodate oxidation (known to abrogate Sia recognition by CD22) also had this unmasking effect, indicating that the effects of desialylation are not due to a loss of negative charge. Normal resting B cells from human peripheral blood gave similar findings. However, the lectin is partially unmasked during in vitro activation of these cells. Thus, the lectin activity of CD22 is restricted by endogenous sialylation in resting B cells and may be transiently unmasked during in vivo activation, perhaps to modulate intercellular or intracellular interactions at this critical stage in the humoral response.